Adoption : changing families, changing times - Douglas, Anthony, 1949-; Philpot, Terry (Routledge, 2003)
Illustrating political and professional issues through stories and contributions from specialist practitioners, this book offers a fully rounded picture of adoption and explores some of the myths surrounding it.